Study on the Bearing of Hot Water Treatment on Seed Germination and Seedling Growth of Albizia proCera Benth - Ali, M. A.; Akhter, S.; Kamaluddin, M. (Indian Forester, 1997)
Seed germination, seedling mortality and subsequent growth of Albizia procera seedlings were studied. Seeds were treated with hot water of 50° and boiled water of lOO°C for three minutes and compared against the untreated seeds soaked in cold water. It was observed that the germination per cent was higher and mortality was lower in the case of untreated seeds. Root/shoot ratio oflength and biomass were not different among thOse seeds. The overall performance was found better in the case of untreated seeds though there was a little advantage in shoot length and root length in the case of lOO°C treated seeds.